Islamic Law of Inheritance among the Yoruba of Southwest Nigeria: A Case Study of Dar ul-Qadha (Arbitration Panel) - Bello, Abdulmajeed Hassan (Journal of Islamic Law, 2024)
This article examines the complex aspects of succession law, which deals with the transmission of rights and obligations of individuals who have deceased concerning their inheritance, based on the legal sources adopted by society. Although the Yoruba succession practices rely on three different legal sources (common law, customary law, and Islamic law), Dar ul-Qadha (arbitration panel) disregards the latter legal source. The study aims to analyse the application of Islamic inheritance law in three cases of private legal disputes resolved by Dar ul-Qadha from 2008 to 2013. Adopting a qualitative and interpretative research method, the research findings reveal that guidelines for property distribution in Islamic law are overlooked by Dar ul-Qadha. Mothers are excluded from inheritance, while uncles, cousins, half-brothers, and step-sisters can inherit alongside full brothers. Moreover, personal property is not considered in the distribution. Neglect of Islamic inheritance law is attributed to the dominance of Yoruba social and cultural life, influenced by colonialism, Christianity, and societal ignorance. Therefore, this article argues that the distribution of inheritance through a valid Islamic system will accommodate the extended cultural family of the Yoruba. Recommendations emphasise the importance of adhering to legal requirements under land law. [Artikel ini meneliti aspek kompleks hukum suksesi, yang menangani transmisi hak dan kewajiban individu yang telah meninggal terkait dengan harta waris mereka, berdasarkan sumber hukum yang diadopsi oleh masyarakat. Meskipun praktik suksesi masyarakat Yoruba bergantung pada tiga sumber hukum yang berbeda (common law, hukum adat dan hukum Islam), Dar ul-Qadha (Dewan Arbitrase), Logos, mengabaikan sumber hukum yang terakhir. Studi ini bertujuan untuk menganalisis penerapan hukum waris Islam dalam tiga perselisihan hukum pribadi yang diselesaikan oleh Dar ul-Qadha dari tahun 2008 hingga 2013. Dengan mengadopsi metode penelitian kualitatif dan interpretatif, temuan penelitian mengungkapkan bahwa panduan distribusi properti dalam hukum Islam diabaikan oleh Dar ul-Qadha. Ibu dikecualikan dari warisan, sementara paman, sepupu, saudara laki-laki dan perempuan tiri dapat mewarisi bersama saudara laki-laki kandung. Selain itu, harta pribadi tidak dipertimbangkan dalam pembagian. Kelalaian terhadap hukum waris Islam ini disebabkan oleh dominasi kehidupan sosial dan budaya masyarakat Yoruba yang dipengaruhi oleh kolonialisme, kekristenan, dan ketidaktahuan masyarakat. Oleh karena itu, artikel ini berargumentasi bahwa pembagian harta peninggalan melalui sistem surat wasiat Islam yang sah dapat mengakomodasi keluarga besar budaya Yoruba. Rekomendasi menekankan pentingnya mematuhi persyaratan hukum dari hukum tanah.]